Fluviispira multicolorata gen. nov., sp. nov. and Silvanigrella paludirubra sp. nov., isolated from freshwater habitats. Issue 3 (6th January 2020) - Pitt, Alexandra; Koll, Ulrike; Schmidt, Johanna; Hahn, Martin W.
Abstract : Strain 33A1-SZDP T was isolated from a small creek located in Puch, Austria. Strain SP-Ram-0.45-NSY-1 T was obtained from a small pond located in Schönramer Moor, Germany. 16S rRNA gene sequence similarities between the type strain of Silvanigrella aquatica, currently the only member of the family Silvanigrellaceae, and strains 33A1-SZDP T and SP-Ram-0.45-NSY-1 T of 94.1 and 99.1 %, respectively, suggested affiliation of the two strains with this family. Phylogenetic reconstructions with 16S rRNA gene sequences and phylogenomic analyses with amino acid sequences obtained from 103 single-copy genes suggested that the strains represent a new genus and a new species in the case of strain 33A1-SZDP T (=JCM 32978 T =DSM 107810 T ), and a new species within the genus Silvanigrella in the case of strain SP-Ram-0.45-NSY-1 T (=JCM 32975 T =DSM 107809 T ). Cells of strain 33A1-SZDP T were motile, pleomorphic, purple-pigmented on agar plates, putatively due to violacein, and showed variable pigmentation in liquid media. They grew chemoorganotrophically and aerobically and tolerated salt concentrations up to 1.2 % NaCl (v/w). The genome size of strain 33A1-SZDP T was 3.4 Mbp and the G+C content was 32.2 mol%. For this new genus and new species, we propose the name Fluviispira multicolorata gen. nov., sp. nov. Cells of strain SP-Ram-0.45-NSY-1 T were motile, pleomorphic, red-pigmented and grew chemoorganotrophically and aerobically. They tolerated salt concentrations up to 1.1 % NaCl (v/w). The genome size of strain SP-Ram-0.45-NSY-1 T was 3.9 Mbp and the G+C content 29.3 mol%. For the new species within the genus Silvanigrella we propose the name Silvanigrella paludirubra sp. nov.